The extended H i halo of NGC 4945 as seen by MeerKAT. Issue 2 (7th April 2022) - Ianjamasimanana, Roger; Koribalski, B S; Józsa, Gyula I G; Kamphuis, Peter; de Blok, W J G; Kleiner, Dane; Namumba, Brenda; Carignan, Claude; Dettmar, Ralf-Jürgen; Serra, Paolo; Smirnov, Oleg M; Thorat, Kshitij; et al.
ABSTRACT: Observations of the neutral atomic hydrogen (H i ) in the nuclear starburst galaxy NGC 4945 with MeerKAT are presented. We find a large amount of halo gas, previously missed by H i observations, accounting for 6.8 per cent of the total H i mass. This is most likely gas blown into the halo by star formation. Our maps go down to a 3 σ column density level of 5 × 10 18 cm −2 . We model the H i distribution using tilted-ring fitting techniques and find a warp on the galaxy's approaching and receding sides. The H i in the northern side of the galaxy appears to be suppressed. This may be the result of ionization by the starburst activity in the galaxy, as suggested by a previous study. The origin of the warp is unclear but could be due to past interactions or ram pressure stripping. Broad, asymmetric H i absorption lines extending throughout the H i emission velocity channels are present towards the nuclear region of NGC 4945. Such broad lines suggest the existence of a nuclear ring moving at a high circular velocity. This is supported by the clear rotation patterns in the H i absorption velocity field. The asymmetry of the absorption spectra can be caused by outflows or inflows of gas in the nuclear region of NGC 4945. The continuum map shows small extensions on both sides of the galaxy's major axis that might be signs of outflows resulting from the starburst activity.